Edge and SOL turbulence and blob variations over a large database in NSTX. (3rd September 2015) - Zweben, S.J.; Davis, W.M.; Kaye, S.M.; Myra, J.R.; Bell, R.E.; LeBlanc, B.P.; Maqueda, R.J.; Munsat, T.; Sabbagh, S.A.; Sechrest, Y.; Stotler, D.P.
Abstract: This paper describes the range of variations in edge and SOL turbulence observed using a gas puff imaging (GPI) diagnostic in NSTX discharges. The database consists of 140 shots including Ohmic, L-mode, and H-mode plasmas measured during steady-state conditions (e.g. without ELMs). Turbulence quantities were evaluated using both cross-correlation analysis and blob tracking. Relative fluctuation levels varied from –1.0, correlation times were –40 μ s, correlation lengths were –10 cm, and turbulence velocities were km s −1 and km s −1 outwards. These variations were evaluated with respect to both the global and local edge plasma parameters, and compared with simplified theoretical models.